The post-2015 debate and the place of education in development thinking - McGrath, Simon (Elsevier, 2014)
As the end date for the Millennium Development Goals approaches so the focus on goals, visions and policies for development after 2015 becomes ever heightened. However, there has been relatively little engagement by educational research community in these debates. What then is being written about education in the key post-2015 documents? How is education's role in development conceptualised by those most central to shaping new accounts? I explore these issues through an analysis of a key text on post-2015, the High Level Panel Report of May 2013 (UN-HLP 2013), and an exploration of a year's worth of posts on 30 prominent blogs and websites discussing post-2015 matters. This leads me to two further, interlinked questions: what are the implications of potential marginalisation and irrelevance from these debates for the field of international education and development research? What are the potential dangers for the field of closer engagement in these debates and their growing use of social media? The academic international education and development community may be more comfortable in keeping these policy debates at a distance, but this may play against the strong educational research drive to engage in social science that makes a difference. If there is to be engagement with post-2015 then alternative ways of developing practices of research, action and dialogue need further strengthened. This may include interdisciplinary dialogues around such issues as early childhood development, the role of professions in development or environmental sustainability. Engagement with the post-2015 debate would also require a careful analysis of how best to engage with the instrumentalised accounts of education that are dominant in the policy-advocacy arena. This would entail more strategic positions on the uses and dangers of social media. At the same time, engagement with development studies as well as the development policy community requires a reappraisal of epistemological and methodological stances.